Nuremberg trials. Analysis of your approach to guilt - López Soria, Yudith (2021)
As of World War II and because of it, humanity also knew a series of trials that were aimed at judging the war crimes that occurred, and the culprits are known, the Nuremberg Trials. In the history of humanity and in the evolution of law, it was an extremely important moment, even marking the birth of the Universal Declaration of Human Rights. Thus, the objective of this work is: Critically review the technical and legal treatment, given the structural element of the crime, guilt, in the conduct of the Nuremberg Trials. Above all, analyzing the legal positions held by the judges who represented the most powerful powers in the world at that time. The result obtained is precisely the critical reflection on the position and roles, observed for the guilt element in the prosecution of these war crimes. This result was obtained through methods such as bibliographic review, documentary, historical-logical and inductive-deductive analysis.